2021
DOI: 10.1097/aog.0000000000004431
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Outcomes of Two Screening Strategies for Gestational Diabetes Mellitus

Abstract: et al. Perinatal outcomes of two screening strategies for gestational diabetes mellitus: a randomized controlled trial. Obstet Gynecol 2021;138. The authors provided this information as a supplement to their article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 34 publications
2
60
1
2
Order By: Relevance
“…However, when using a two-step screening strategy with GCT, a 100g OGTT is only needed in about 20% of all pregnant women. In line with normal clinical practice, adverse events of the screening tests would therefore occur in only 4% of women using a two-step screening strategy with GCT compared to 13% in women undergoing the one-step IADPSG approach with OGTT (11). Women who preferred a GCT or two-step screening strategy had a better metabolic profile (were less often obese and less insulin resistant) and had less risk factors for GDM compared to women who preferred an OGTT or one-step screening approach.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, when using a two-step screening strategy with GCT, a 100g OGTT is only needed in about 20% of all pregnant women. In line with normal clinical practice, adverse events of the screening tests would therefore occur in only 4% of women using a two-step screening strategy with GCT compared to 13% in women undergoing the one-step IADPSG approach with OGTT (11). Women who preferred a GCT or two-step screening strategy had a better metabolic profile (were less often obese and less insulin resistant) and had less risk factors for GDM compared to women who preferred an OGTT or one-step screening approach.…”
Section: Discussionmentioning
confidence: 72%
“…Evidence is lacking that treatment of GDM based on the one-step IADPSG screening approach improves pregnancy outcomes compared to other screening strategies. Recently, two large RCT’s from the US showed that a one-step screening strategy with the IADPSG criteria leads to a 2-3 fold increase in GDM prevalence compared to screening with a two-step approach with GCT but without improvement of pregnancy outcomes ( 11 ). In addition, the OGTT is often considered a cumbersome test during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, many European countries still use selective screening for GDM based on risk factors or recommend a twostep screening strategy with a glucose challenge test (GCT) (10). In addition, evidence is lacking that treatment of GDM based on the IADPSG screening strategy improves pregnancy outcomes compared to other screening strategies (11,12). Moreover, a GCT is generally better tolerated than an OGTT and has the advantage that it can be performed in a non-fasting state (12).…”
Section: Introductionmentioning
confidence: 99%